Transient receptor potential protein subunit assembly and membrane distribution in human platelets - Brownlow, Sharon L.; Sage, Stewart O. (Thrombosis and Haemostasis, 2005)
We have previously suggested that the human homologue of theDrosophila transient receptor potential protein, TRPC1, is involved in conducting store-operated Ca2+ entry (SOCE) in human platelets since an antibody raised against the poreforming region of TRPC1 inhibited SOCE. Here we have investigated plasma membrane expression of TRPC1 in human platelets and have probed for the presence of otherTRPC proteins in these cells. Biotinylation revealed the presence of TRPC1 in the plasma membrane of resting platelets. Surface expression was not detectibly changed following Ca2+ store depletion or stimulation with thrombin. Western blotting demonstrated the presence of TRPC1, TRPC3, TRPC4, TRPC5 and TRPC6 in platelet lysates. TRPC1, TRPC4 and TRPC5 coimmunoprecipitated, as did TRPC3 and TRPC6. TRPC1, TRPC4 and TRPC5 were associated with detergent-resistant platelet membranes, from which they were partially released when the cells were cholesterol-depleted using methyl-β-cyclodextrin. The distributions of TRPC3 and TRPC6 between soluble and membrane fractions were not affected by methyl-β-cyclodextrin treatment. These results suggest that TRPC1,TRPC4 and TRPC5 form a heteromultimer associated with platelet lipid raft domains, whereas TRPC3 and TRPC6 associate independently of lipid rafts.
Keywords: Platelet physiology; signal transduction; thrombin